2020
DOI: 10.3390/rs12244050
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Experiment Observations of Ionospheric Disturbances as Precursory Effects of the Indonesian Ms6.9 Earthquake on August 05, 2018

Abstract: Taking the 2018 Ms6.9 Indonesia earthquake as a case study, the ionospheric perturbations in very low frequency (VLF) transmitters recorded by China Seismo-Electromagnetic Satellite (CSES) were mainly investigated, as well as the multi parameters of the plasma and electromagnetic field. The characteristics of electron density (Ne), GPS TEC, ULF electric field, ion drift velocity, and ionosphere height were extracted and compared with the features of the signal-noise ratio (SNR) from VLF transmitters of NWC at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The lowering of the D-region ionospheric boundary alters the conditions for the VLF modal interference (Maurya et al, 2016). Zhang et al (2020) for Indonesian EQ on August 5, 2018 found that the nighttime ionospheric height around the EQ epicenter reduced from 26 July to 9 August to 85 km as compared to 95 km from 15 to 25 July.…”
Section: Discussionmentioning
confidence: 99%
“…The lowering of the D-region ionospheric boundary alters the conditions for the VLF modal interference (Maurya et al, 2016). Zhang et al (2020) for Indonesian EQ on August 5, 2018 found that the nighttime ionospheric height around the EQ epicenter reduced from 26 July to 9 August to 85 km as compared to 95 km from 15 to 25 July.…”
Section: Discussionmentioning
confidence: 99%
“…The time frame could be from a few weeks, days, up to hours-in any case as much as possible steady conditions-and also depends on the time of the preparation phase of an, e.g., earthquake. This implies, at first glance, that carrying out and comparing such models are not fully useful, narrow preand post-spatio-temporal high-quality samplings in multi experiment settings and complementary measurements are preferable [9,10]. The 1 Hz magnetic field data from CSES HPM permit the analysis of large scale structures, whereas the Swarm VFM 50 Hz high rate values enable the study of, e.g., fine structured details during boundary crossings in the ionosphere above target objects on the ground.…”
Section: Magnetic Field Models and Multi-experiments Observationsmentioning
confidence: 99%
“…From the comparisons between CSES Ne and other observations/models (Wang et al, 2019;Yan et al, 2020;Liu et al, 2021), it confirms that the Ne data can reliably reveal the ionospheric characteristics at the satellite altitude of 507 km. So far, using the CSES data, some case studies of seismo-ionospheric disturbances have been reported (e.g., Yan et al, 2018;Piersanti et al, 2020;Song et al, 2020;Zhang et al, 2020). A statistical study was carried out by Li et al (2020) based on 1-year Ne data.…”
Section: Introductionmentioning
confidence: 99%